Detection of Single Ag Nanoparticles Using Laser Desorption/Ionization Mass Spectrometry - Žalud, Michal; Prysiazhnyi, Vadym; Bednařík, Antonín; Preisler, Jan (Journal of the American Society for Mass Spectrometry, 2023)
The detection of a single entity (molecule, cell, particle, etc.) was always a challenging subject. Here we demonstrate the detection of single Ag nanoparticles (NPs) using subatmospheric pressure laser desorption/ionization mass spectrometry (LDI MS). The sample preparation, measurement conditions, generated ions, and limiting experimental factors are discussed here. We detected from 84 to 95% of the deposited 80 nm Ag NPs. The presented LDI MS platform is an alternative to laser ablation inductively coupled plasma mass spectrometry for imaging distribution of individual NPs across the sample surface and has a great potential for multiplexed mapping of low-abundance biomarkers in tissues.